(untitled) (World Bulletin of Management and Law, 2023)
This scientific article covers the present-day age of information, the concept of cyberspace, aspects of its emergence in detail. Particular emphasis is placed on the content disclosure of considered emodzi, one of the modern objects of cyberspace. Also, the signs of emoji associated with cyberspace, scientific research work on this matter, opinions of scientists are analyzed in detail. Moreover the protection of intangible favors, national and foreign norms in regulation and their importance are comprehensively highlighted. Also, the calculation of emoji in cyberspace as the result of intellectual activity, the fact that it is an object of intellectual property was studied on the basis of a number of scientific sources, as well as the opinions of a number of scientists